1987
DOI: 10.1254/jjp.44.135
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Two Forms of γ-Oryzanol in Different Sterol Compositions on Hyperlipidemia Induced by Cholesterol Diet in Rats

Abstract: Abstract-Hypolipidemic effects of the usual r-oryzanol (r-OZ) and a new r-OZ (N-r-OZ) with a different sterol composition from r-OZ were investigated on the hyperlipidemia induced by ingestion of a high cholesterol diet (HCD) containing 1 % cholesterol for 12 days in male Sprague-Dawley rats. Treatment with r-OZ for 6 days significantly inhibited the increase in serum total cholesterol (TC) and phospholipids (PL) induced by HCD, while the treatment with r-OZ for 12 days did not inhibit the increase of TC and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 15 publications
1
37
1
2
Order By: Relevance
“…In the previous study, we reported that the hypolipidemic effect of OZ may be mainly produced by the CAF among the different sterols in the composition of this compound (6). The present study was designed to demonstrate this inference, and the effect of See explanation in Fig.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In the previous study, we reported that the hypolipidemic effect of OZ may be mainly produced by the CAF among the different sterols in the composition of this compound (6). The present study was designed to demonstrate this inference, and the effect of See explanation in Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Methods: Rats were made hyperlipidemic by a HCD containing 1 % cholesterol (6). Control rats were fed commercial food pellets (Nippon Clea Co., Ltd., Tokyo).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Test doses of OZ were selected for rats (50 and 100 mg/kg b. w., p.o.) based on the published literature reports Nakayama et al, 1987).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The chemical structure consists of ferulic acid and sterol or triterpene alcohols such as cycloartenol and 24-methylenecycloartanol connected by ester bonding. GO has been reported to decrease plasma and serum cholesterol (Yoshino et al, 1989;Gerhardt and Gallo, 1998), decrease cholesterol absorption (Seetharamaiah et al, 1990) decrease platelet aggregation (Nakayama et al, 1987) and effectively treat hyperlipidemia (Murase and Lishima, 1963). Its antiinflammatory and anti-tumor was also reported which is related to its antioxidant properties (Juliano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%